Intravitreal S100B Injection Leads to Progressive Glaucoma Like Damage in Retina and Optic Nerve - Kuehn, Sandra; Meißner, Wilhelm; Grotegut, Pia; Theiss, Carsten; Dick, H. Burkhard; Joachim, Stephanie C. (Frontiers in Cellular Neuroscience, 2018)
The glial protein S100B, which belongs to a calcium binding protein family, is up-regulated in neurological diseases, like multiple sclerosis or glaucoma. In previous studies, S100B immunization led to retinal ganglion cell (RGC) loss in an experimental autoimmune glaucoma (EAG) model. Now, the direct degenerative impact of S100B on the retina and optic nerve was evaluated. Therefore, 2 µl of S100B was intravitreally injected in two concentrations (0.2 and 0.5 µg/µl). At day 3, 14 and 21, retinal neurons, such as retinal ganglion cells (RGCs), amacrine and bipolar cells, as well as apoptotic mechanisms were analyzed. Furthermore, neurofilaments, myelin fibers and axons of optic nerves were evaluated. In addition, retinal function and immunoglobulin G (IgG) level in the serum were measured. At day 3, RGCs were unaffected in the S100B groups, when compared to the PBS group. Later, at days 14 and 21, the RGC number as well as the β-III tubulin protein level was reduced in the S100B groups. Only at day 14, active apoptotic mechanisms were noted. The number of amacrine cells was first affected at day 21, while the bipolar cell amount remained comparable to the PBS group. Also, the optic nerve neurofilament structure was damaged from day 3 on. At day 14, numerous swollen axons were observed. The intraocular injection of S100B is a new model for a glaucoma like degeneration. Although the application site was the eye, the optic nerve degenerated first, already at day 3. From day 14 on, retinal damage and loss of function was noted. The RGCs in the middle part of the retina were first affected. At day 21, the damage expanded and RGCs had degenerated in all areas of the retina as well as amacrine cells. Furthermore, elevated IgG levels in the serum were measured at day 21, which could be a sign of a late and S100B independet immune response. In summary, S100B had a direct destroying impact on the axons of the optic nerve. The damage of the retinal cell bodies seems to be a consequence of this axon loss.